A Systematic Literature Review of Apology and Request Strategies in the EFL Context - Kulsawang, Pikul; Ambele, Eric A. (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study aims to examine the diverse strategies employed in apology and request, investigate the influence of cultural factors, social power, and social distance on these strategies, and explore the existing limitations and gaps in the literature for future research. Data collection is conducted using the qualitative technique. Qualitative content analysis is employed for data analysis. The SLR process provides a structured framework for analyzing various strategies employed in speech actsÂ and investigates the impact of cultural variables and social distance on these strategies. Through the implementation of a predetermined review procedure, a total of 16 papers published between 2018 and 2022 were identified and analyzed.Â The findings demonstrated that many studies examined apologies and requests using different strategies and sub-strategies. Notably, politeness usage by Indonesian English teachers reflected social power dynamics, while linguistic strategies among Thai students and EFL learners were shaped by social distance. Thai study underscored the importance of cultural immersion, variations among interactants, and teaching factors in pragmatic competence. The PRISMA-guided systematic review effectively synthesized existing literature. The gaps, novel insights, and unresolved issues identified provided a roadmap for researchers to propel the field forward. This systematic review contributed a snapshot of current knowledge, charted a course for future investigations, identified gaps, and leveraged the strengths of systematic approaches.